How the Comparison of Small Side Games with Team Game Tournament to Improv Handball Playing Skills? - Mukhlisin, Mukhlisin; Dede, Dede; Slamet, Suherman (TEGAR: Journal of Teaching Physical Education in Elementary School, 2023)
Using the right training method can maximize an athlete's talents and achievements to peak performance, the training method used can optimize a skill. The aim of this research is to determine the comparison of the SSG and TGT training methods on handball playing skills. The method used in this research was an experiment. Sampling used a saturated sampling technique. The instrument in this research for Handball playing skills uses The Handball Tactical Performance Evaluation (HTPE). The results of the analysis of athletes belonging to the SSG and TGT groups experienced a more significant increase in playing handball with a sig value of 0.000, however those belonging to the SSG group did not have a significant effect on the Sig value. of 0.859 which is greater than α 0.05. However, the SSG group gave an increase, although not big. The use of SSG training can be examined further across age and gender ranges at a later date to maximize research results.